Analisis Kebutuhan Pengembangan Bahan Ajar berbasis Aplikasi Android tentang Cerita Anak bermuatan Profil Pelajar Pancasila di Sekolah Dasar - Decenni Amelia; Isah Cahyani; Kama Abdul Hakam; Cepi Riyana (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The purpose of this study is to analyze the need for companion teaching materials based on Android applications about children's stories containing the Pancasila Student Profile which are designed to increase reading interest in 4th grade elementary school students. This type of research is descriptive qualitative. The data in this research was obtained through interviews with class IV teachers and also through distributing questionnaires to class IV students at SDN Jakasampurna IV, Bekasi City. Based on the results of interviews with teachers, teachers really need accompanying teaching materials to increase students' interest in reading, because so far teachers still rely on textbooks, there has never been an Android application-based teaching material about children's stories containing the Pancasila Student Profile. Meanwhile, students are also known to need accompanying teaching materials in the form of Android applications because students prefer to open their cellphones rather than read textbooks. Students find textbooks very monotonous and not interesting to read. Based on the results of the analysis of teacher and student needs, it is necessary to develop Android application-based teaching materials about children's stories containing the Pancasila Student Profile to increase reading interest in fourth grade elementary school students.